Hyaluronic acid oligosaccharide-modified collagen nanofibers as vascular tissue-engineered scaffold for promoting endothelial cell proliferation. (1st November 2019) - Kang, Lingzhi; Jia, Weibin; Li, Min; Wang, Qin; Wang, Chuandong; Liu, Yang; Wang, Xianpeng; Jin, Lan; Jiang, Jianjun; Gu, Guofeng; Chen, Zonggang
Highlights: The hyaluronic acid oligosaccharides (oHAs) modified collagen were fabricated. We report the characterizations of HA-modified collagen electrospun nanofibers. The PIECs could maintain their characteristic phenotypes on the electrospun scaffolds. The oHAs-modified collagen nanofibers could promote PIECs proliferation. Abstract: Hyaluronic acid oligosaccharides (oHAs) have shown promising results in promoting vascular endothelial cell (EC) proliferation and endothelialization. To engineered develop tissue scaffold for promoting EC proliferation and vessel endothelialization, different sizes of oHAs were prepared and grafted onto collagen to improve the biological properties of the synthesized materials, especially in angiogenesis. Firstly, oHAs were successfully prepared and conjugated with collagen to construct glycosylated collagens by reductive amination. The glycosylated collagens were then electrospun into various nanofibrous structures and their morphology and hemocompatibility, as well as EC responses on these nanofibrous scaffolds, were studied to evaluate the potential for vascular tissue engineering. The results showed that the nanofibrous scaffolds grafted by oHAs promoted EC proliferation whereas high molecular weight HA inhibited proliferation. The scaffolds had no detectable degree of hemolysis and coagulation, suggesting their promise as engineered vascular tissue scaffolds.